UPAYA GURU DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL ANAK KELOMPOK B TK MALLUSETASI KECAMATAN TELLUSIATTINGE KABUPATEN BONE - S, Srinita; Mahmud, Bonita (EDUCHILD (Journal of Early Childhood Education), 2022)
AbstractThis study aims to determine the teacher's efforts in developing children's social skills and the things that are supporting and inhibiting factors for teachers in developing social skills in group B children at Mallusetasi Kindergarten, Tellusiattinge District, Bone Regency. This research is qualitative, where the data sources are teachers and students in Group B Mallusetasi Kindergarten, Tellusiattinge District, Bone Regency. The data collection techniques used are observation and interviews. The results of the study show that there are several teacher efforts in developing social skills for children in group B kindergartens in Mallusetasi, Tellusiattinge District, Bone Regency, namely by social playing, providing opportunities for children to carry out social interactions, and providing facilities and infrastructure that can support the process of stimulating children's social skills. The supporting factors in the process of developing the social skills of Group B children at Mallusetasi Kindergarten, Tellusiattinge District, Bone Regency are the enthusiasm that the children have and the motivation given by the teacher. While the inhibiting factors experienced by teachers in developing children's social skills, such as the child's emotional state, which sometimes brings negative emotions from home, and the lack of attention of children during the learning process